Pengembangan Startup Sunar Farm Dengan Metode Design Sprint - I Putu Teja Artadi; I Gede Juliana Eka Putra; Tiawan Tiawan (STMIK Pringsewu, 2022)
Sunar Farm is a startup that provides tools for trapping pests and rat repellents on rice plants, which is currently under the guidance of the STMIK Primakara business incubator. Startup Sunar Farm is experiencing problems in sales, there is still no interest from farmers in buying Sunar Farm equipment. The solution that is trying to be applied to these problems is by developing and mapping the business model of the Sunar Farm startup using the Design Sprint method. The Design Sprint method is used to find solutions, validate the problems of Startup Sunar Farm, and use BMC to map changes in the business model of the solutions obtained. The Design Sprint method has 5 stages consisting of understanding to understand the user's problems, the divergence stage to make solutions to existing problems, the decide voting stage for the solution, the prototype stage, namely making the physical form of the selected solution, and the validate stage validating the prototype made. The results of this study using the Design Sprint method obtained several additions to the BMC, namely additions to the customer segment, value propositions, channels, customer relationships, and key partnerships.